2015
DOI: 10.1016/j.bbamem.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lys to Glu mutations in GsMTx4 on membrane binding, peptide orientation, and self-association propensity, as analyzed by molecular dynamics simulations

Abstract: GsMTx4, a gating modifier peptide acting on cationic mechanosensitive channels, has a positive charge (+5 e) due to six Lys residues. The peptide does not have a stereospecific binding site on the channel but acts from the boundary lipids within a Debye length of the pore probably by changing local stress. To gain insight into how these Lys residues interact with membranes, we performed molecular dynamics simulations of Lys to Glu mutants in parallel with our experimental work. In silico, K15E had higher affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 40 publications
(64 reference statements)
3
30
0
Order By: Relevance
“…We predicted that this creates a reservoir of mobile surface area on one monolayer which would have the effect of clamping the tension on that monolayer which was further supported by molecular dynamic simulations (Fig. 2 and [75]). A new model of GsMTx4 inhibition is proposed where the critical factors for its inhibitory potential are how deeply it binds to relaxed membranes and its availability to transition to deeper states as tension increases.…”
Section: Gsmtx4 Mechanism Of Inhibition and Modulation Of Piezo Vs K+mentioning
confidence: 63%
“…We predicted that this creates a reservoir of mobile surface area on one monolayer which would have the effect of clamping the tension on that monolayer which was further supported by molecular dynamic simulations (Fig. 2 and [75]). A new model of GsMTx4 inhibition is proposed where the critical factors for its inhibitory potential are how deeply it binds to relaxed membranes and its availability to transition to deeper states as tension increases.…”
Section: Gsmtx4 Mechanism Of Inhibition and Modulation Of Piezo Vs K+mentioning
confidence: 63%
“…We have shown that GsMTx4 associates superficially with membranes under low tension, and inserts deeper when membrane tension increases acting as an area/tension clamp for the outer monolayer [21,22]. Recent electron micrographic studies of the Piezo1 channel structure place the likely mechanosensing domains for these channels on the outer monolayer [59].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro measures of MSC activity in cardiac tissue, single cells and patch assays, show GsMTx4 activity in the range of 0.1–5 μM [15,19,20]. GsMTx4 is a gating modifier that inhibits MSCs by clamping the membrane tension of the outer monolayer where its penetration depth, and thus its surface area contribution, is tension dependent [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Independent of resolution of the force field used, classical (i.e., unbiased) MD simulation are used to address questions including, but not limited to, the spontaneous binding of the peptide to the membrane surface, including conformational changes in the peptide, the penetration‐depth and orientation of the peptide at the water–lipid interface, the identification of peptide residues that control lipid binding, the effect of peptide binding on the local structure of the membrane, and the effect of lipid composition or mutations in the peptide on these properties. For pore‐forming peptides, classical MD simulations are also used to study the structure and stability of preformed pores or the first steps in pore formation …”
Section: Computational Approaches To Study Venom Peptide—membrane Intmentioning
confidence: 99%
“…Like GMs, MSC‐directed peptides are mostly disulfide‐rich peptides with a well‐defined secondary structure. Examples include the spider venom peptides GasFII, GsMTx‐2, and GsMTx‐4 . The third group are pore‐forming peptides that irreversibly damage cell membranes by a pore‐forming mechanism (Figure ).…”
Section: Introductionmentioning
confidence: 99%